Переваги та недоліки класифікації одягу на відвідувачах по їх зображенням - Кравченко, Д. С. (ХНУРЕ, 2024)
This work is devoted to the analysis of the advantages and disadvantages of using computer vision for the classification of objects, in particular, in the clothing of web application users. Let’s consider various options for using this technology in everyday life, paying attention to its potential and limitations. The study will also cover modern technological solutions already implemented in the market and compare their effectiveness with traditional methods. In addition, we will analyze the impact of computer vision on user interaction with online platforms and the possibilities of its future improvement. Highlighting these aspects will help to understand how this technology can affect our daily life realities and contribute to the development of modern Internet services.
Keywords: класифікація одягу; зображення одягу